1994
DOI: 10.1002/j.1460-2075.1994.tb06639.x
|View full text |Cite
|
Sign up to set email alerts
|

Roles of RNase E, RNase II and PNPase in the degradation of the rpsO transcripts of Escherichia coli: stabilizing function of RNase II and evidence for efficient degradation in an ams pnp rnb mutant.

Abstract: The Escherichia coli rpsO gene gives rise to different mRNA species resulting either from termination of transcription or from processing of primary transcripts by RNase E and RNase III. The main degradation pathway of these transcripts involves a rate‐limiting RNase E cleavage downstream of the structural gene which removes the 3′ terminal stem‐loop structure of the transcription terminator. This structure protects the message from the attack of 3′‐5′ exonucleases and its removal results in very rapid degrada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
126
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(139 citation statements)
references
References 73 publications
12
126
0
1
Order By: Relevance
“…Although RNase R and PNPase are not known to work together, our data suggests that these enzymes may cooperate to convert the ϩ19 cleavage product to the ϩ13 product. Finally, RNase II can indirectly inhibit the degradation of structured mRNAs by removing 3Ј single-stranded regions required by PNPase to bind substrate (39,40). These biochemical properties are consistent with the accumulation of cleavage products in our exoribonuclease knock-out strains.…”
Section: Discussionsupporting
confidence: 84%
“…Although RNase R and PNPase are not known to work together, our data suggests that these enzymes may cooperate to convert the ϩ19 cleavage product to the ϩ13 product. Finally, RNase II can indirectly inhibit the degradation of structured mRNAs by removing 3Ј single-stranded regions required by PNPase to bind substrate (39,40). These biochemical properties are consistent with the accumulation of cleavage products in our exoribonuclease knock-out strains.…”
Section: Discussionsupporting
confidence: 84%
“…Ten micrograms of total RNA were separated either on 1% agarose formaldehyde gel or 6% polyacrylamide gels for mRNA and sRNA analysis, respectively, and analyzed by Northern blotting (Hajnsdorf et al 1994;Hajnsdorf and Régnier 1999). Templates for the synthesis of ArcZ, GcvB, SgrS, and oppA and ptsG RNA probes were obtained by PCR amplification using a oligonucleotide containing the T7 promoter and a RNA-specific oligonucleotide (indicated with prefix m) described in Supplemental Table S2.…”
Section: Rna Preparation Analysis and Labelingmentioning
confidence: 99%
“…This indicated that the possible pairing of SraG-S or SraG to rpsO and rpsO-pnp transcripts did not affect the RNase E cleavage of the mRNA upstream of the terminator T1 (Fig. 1C), which is the limiting step in the degradation of the rpsO transcript (Régnier and Hajnsdorf 1991;Hajnsdorf et al 1994b). In addition, asRNA overproduction did not significantly affect RNase III cleavage efficiency at the RIII1 site (Figs.…”
Section: Srag Srna Participates In Pnpase Homeostasismentioning
confidence: 92%
“…The levels of the rpsO transcript were lower in the rnc mutant. This is presumably because the level of PNPase was higher in the rnc strain and because PNPase was responsible for the poly(A)-dependent degradation of the rpsO transcript (Hajnsdorf et al 1994b;Robert-Le Meur and Portier 1994). This decrease was partly rescued by overproduction of either SraG or SraG-S, suggesting that they could negatively control the level of PNPase.…”
Section: Srag Srna Participates In Pnpase Homeostasismentioning
confidence: 99%